Impacto de la facturación electrónica en la empresa exportadora de banano Traboar S.A. - Behr Toro, Hortencia del Rosario (2015)
Electronic invoicing is a method to remove barriers and simplify the task of fiscal policy, its origin is oriented and viable route accounting and tax processes more simple, but the implementation and change cause instability and fear, trainings when they are not really efficient support for the implementation of a system that is totally unknown, inexperience of staff and lack of controls to safeguard the reliability of the processes continuously increase the margin of error and generate in employees a level of intense pressure . The importance of adoption is highlighted in scientific research as what induces firms to adopt e-invoicing? Effect of perceptions and the competitive environment, the purpose of the tax administration has always been to optimize time, resources, human talent, and improve operational and competitive status of each company and this is an effective way to find and on the invoice electronics in Spain, the impact being created by implementing this system within enterprises in some US states. This is a work that is part of the quantitative methodology. It aims to design a scheme to be used to measure and control the accounting and tax processes. The main conclusion obtained is continuous typing errors that generate the cancellation of invoices in an unreasonable amount. The main recommendation is that this resource is used as evaluation continually so that the accounting process is conducted properly.